Optimizing the Role of Body-Bathers as a Priority for Zakat al-Fitr Recipients in Sikilang, Sungai Aur Pasaman Barat - Putra, Dedisyah; Tambunan, Jannus (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This research analyzes the practice of bathing corpse carried out in Sikilang Village, Sungai Aur Kuning Pasaman Barat District, which is in accordance with zakat al-fitr. This is a phenomenological and qualitative research with data collected through observation and in-depth interviews to determine the distribution of zakat al-fitr in accordance with maqashid. The results showed that body-bathers in Sikilang village do not have a fixed wage, hence many people are reluctant to pursue this profession. Furthermore, the review of maqasid shari'ah that customs can be used as an instrument in establishing law with terms and conditions set by the scholars. In conclusion, the habit of the people prioritizing body-bathers as the recipient of zakat al-fitr is contrary to al-nushus al-shari'ah.